Post a New Question

math problem

posted by .

please help

Simplify

Multiply

(2ã7-4ã2)(5ã7+10ã2)

  • math problem -

    Assuming your garbled symbol means √, we have

    (2√7 - 4√2)(5√7 + 10√2)
    just think of these as polynomials in x and y

    (2x-4y)(5x+10y) = 10x^2 - 40y^2

    letting x = √7 and y = √2, we have

    10(√7)^2 - 40(√2)^2 = 10*7-40*2 = -10

    Some work could have been saved by noting that

    (2√7 - 4√2)(5√7 + 10√2)
    = 2(√7-2√2) * 5(√7+√2)
    = 10(√7-2√2)(√7+2√2)
    = 10(7-8)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  2. fractions

    my teacher gave us some fraction problems for homework, but I'm confused about how to go about solving the problem. The problem is what is 2/4 of 8. Can you show me the steps so I can do the rest of the math problems?
  3. math

    Can someone help me with this problem? multiply and simplify 4 1/5 x 10/21 x 9/20. I know after you simplify 4 1/5 it will be 21/5. What is the next step.
  4. Math 116 Axia

    rewrite using multiplication -70/(23) Do not simplify, Type a fraction I can multiply and divide but I am not sure how to work the problem. can someone do a problem with the same type of values so I can see the steps involved?
  5. Algebra (check my answers)

    Please check these answers. Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 - 11y - 6x - 9 - y = 6x - 12y - 5 Evaluate the expression …
  6. Algebra

    Can you please check my work? You have helped other students I know. Thank you:) Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 -
  7. Math

    Multiply and Simplify: (a^x-a^(-x))^3 =(a^x-a^(-x))(a^x-a^(-x))(a^x-a^(-x)) =(a^x-a^(-x))(a^2x-a^0-a^0+a^(-2x)) =(a^x-a^(-x))(a^2x-2+a^(-2x)) =a^3x-2a^x+a^(-x)-a^x+2a^(-x)-a^(-3x) =a^3x-3a^x+3a^(-x)-a^(-3x) =?
  8. Math Problem

    please help simplify Multiply (6x+1)(7x^2+5x+4)
  9. Math Problem

    Please multiply and simplify the answer I am having trouble with (3x+7)(4x^2+2x+8)
  10. math problem

    please help Multiply and simplify answer (v+f)(v^2-vf+f^2)

More Similar Questions

Post a New Question